Effect of dance on social physique anxiety and physical self-esteem among adults: a systematic review - Liu, Xutao; Soh, Kim Geok; Lu, Yingjie (Frontiers in Psychology, 2025)
BackgroundPhysical activity has been widely recognized for its positive impact on mental health. Dance, as a form of physical activity, has garnered increasing attention in recent years. Existing literature suggests that dance specifically contributes to enhancing physical wellbeing and promoting emotional development. This systematic review aims to assess the impact of dance on social physique anxiety and physical self-esteem in adults.MethodA systematic literature search was conducted across multiple academic databases, including Embase, EBSCOhost, Cochrane, Scopus, PubMed, and Web of Science. The data were then systematically reviewed using the PRISMA guidelines. The quality of each study's appraisal was evaluated using the PEDro scale.ResultsSixteen studies examined the effects of seven types of dances—Zumba, Latin dance, Salsa, Dance Movement Therapy, Aerobic dance, Belly dance, and Colombian Caribbean Folk dance—on adult's social physique anxiety and physical self-esteem. The participants in this review included adults, college students and older adults (ages range from 18 to 76). The quality appraisal scores on the PEDro scale ranged from 3 to 6. Dance interventions were found to significantly enhance physical self-esteem and self-confidence, while concurrently reducing social physique anxiety and negative self-evaluation in an enjoyable manner.ConclusionThis review indicates that dance positively affected social physique anxiety and physical self-esteem for experimental groups that participated in dance compared to control groups in the reviewed studies. These effects were consistent across all age groups. Moreover, the study demonstrates that female participants in the experimental groups experienced more significant improvements in physical self-esteem and greater reductions in social physique anxiety levels compared to male participants.Systematic review registrationhttps://www.crd.york.ac.uk/prospero, identifier: CRD42022315034.